THE KOMBINASI ISCHEMIC COMPRESSION TECHNIQUE DENGAN CRYOTHERAPY SAMA BAIK DENGAN CONTRACT RELAX STRETCHING DALAM MENURUNKAN NYERI PADA SINDROM MYOFASCIAL OTOT UPPER TRAPEZIUS PADA MAHASISWA FISIOTERAPI FK UNUD - Putu Ayu Sita Saraswati; Sutha Nurmawan; Ni Wayan Tianing (Majalah Ilmiah Fisioterapi Indonesia, 2015)
The research was aimed to compare the combination of ischemic compression technique and cryotherapy with contract relax stretching in decreasing pain of myofascial pain syndrome in upper trapezius muscle. This research was an experimental study with Randomized Pre and Post Test Group Design. Samples were divided into 2 treatment group that consist 10 samples for each. The first group treated with combination of ischemic compression technique with cryotherapy while the second one was treated with contract relaxes stretching. The results showed there was significant effect of each treatment to decrease pain p = 0.0001 ( p < 0.05 ). The results of independent t test showed p=0,598 (p > 0,05), so that there was no significant difference from decreased pain group 1 (combination of ischemic compression technique with cryotherapy) and group 2 (contract relax stretching). The first group mean’s was 2.650±1.051 whereas the second group mean’s was 3.120±1.091. In conclusion, the combination of ischemic compression technique with cryotherapy is as effective as contract relax stretching for decreasing pain of myofascial pain syndrome in upper trapezius at Department of Physical Therapy’s students of Udayana University